Minitmithing Kapayapaan: An Interpretative Phenomenological Analysis of Posttraumatic Growth Among Military Personnel Who Fought in the Marawi Siege - Jacob, Alvin (Social Sciences and Development Review, 2023)
This paper focused on the posttraumatic growth of soldiers deployed in the Marawi Siege in 2017, the First Scout Ranger Regiment (FSSR) unit, considered the military’s elite squad. Psychologists Tedeschi and Calhoun posited that a positive change follows a traumatic life event leading to a personality transformation in the individual, thus facilitating growth. The study explored how the soldiers’ involvement in the war resulted in their more profound connection to the Divine Being. The experience made them have a more meaningful relationship with the people they love, appreciate their lives more, and accept their current situation and the responsibilities that go with it.